Heuristic Techniques On Weight Optimization Of Backpropagation Neural Network - Latifah, Khoiriya va (Universitas Islam Sultan Agung, 2018)
The number of visitors the immigration office who made passport or passport renewal every month is very volatile, this problems make the Immigration Office maintain quality of service, thus requiring prediction methods when there will be a surge of visitors so that the quality of service is maintained. The immigration office should have some information to make predictions. Perfect information will make it easier , good predictions and accurate predictions. The exact method is one of the method predict accurately. Its called artificial neural network that a computational method mimics system of neural network biology. Artificial neural networks are formed to solve a particular problem such as pattern recognition or classification because of the learning process. This study uses Heuristic Backpropagation to increase the speed of the training process of neurons in making predictions.